The Influence of The use of Google and Libraries on Students' Learning Outcomes in Social Subjects Class VII of SMP Negeri 6 Pematang Siantar - Yuni Lecia Sianturi (International Journal of Integrated Science and Technology, 2023)
The aim of this research was to determine the "Effect of the Use of Google and Libraries on the Learning Outcomes of Social Sciences Subjects for Class VIII Students of SMP Negeri 6 Pematang Siantar". This research uses quantitative descriptive research. Class VIII students of SMP Negeri 6 Pematang Siantar with a total of 171 students constitute the population in this study. Sampling in this study used a total sampling technique. By using this sampling technique, the students who will be the samples in this study were 171 students consisting of classes VIII-1, VIII-2, VIII-3, VIII- 4, VIII-5. Data collection techniques use questionnaires and documentation. The hypothesis making technique uses multiple linear regression analysis. The results of this study show that: 1) There is a positive and significant influence from the use of Google on the learning outcomes of social studies subjects, seen from the t test where the tvalue from the use of Google (16.394) > ttable value (1.65381) which means this variable significant. 2) There is a positive and significant influence from the library on the learning outcomes of social studies subjects, seen from the t test where the value of library tcount (12.658) > ttable (1.65381) which means the variable is significant. 3) the use of Google and libraries together influences the learning outcomes of social studies subjects, seen from the Ftest where the Fcount value (330.329) > Ftable value (3.048). The R Square coefficient of determination test was found to be 0.797,which means that 79.7% of the Google and library utilization variables influence the learning outcomes of social studies subjects at SMP Negeri 6 Pematang Siantar and the remaining 20.3% is the influence of other variables not examined in this research. The regression value is 2149.521, while the residual value is 546.607, which means there are other factors that influence the learning outcomes of social studies subjects but were not studied in this study, namely 546.607. The results of the multiple regression analysis test are Y = 21.777 +0.401X1 + 0.299X2 + 546.607, which means that variable X1 (use of Google) with a value of 0.401 has a more dominant influence than variable X2 (library) with a value of 0.299.